Oral commercial Chinese polyherbal preparations combined with conventional biomedicine for pulmonary tuberculosis: network meta-analysis - Jiang, Jiankang; Zhang, Siqi; Wang, Hui; Zhang, Lu; Li, Zegeng; Tong, Jiabing; Wu, Fan (Frontiers in Pharmacology, 2025)
BackgroundDespite therapeutic interventions, tuberculosis (TB) remains a persistent challenge. Combination therapy integrating Traditional Chinese Medicine (TCM) with conventional anti-TB medications demonstrates therapeutic benefits, necessitating a meta-analysis evaluating the adjunctive use of oral commercial Chinese polyherbal preparation (CCPP).ObjectivesThis study aims to evaluate the efficacy and safety of different oral TCMs combined with biomedicine for tuberculosis treatment, utilizing network meta-analysis techniques.MethodsA computer-based search was conducted across various databases including the China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, SinoMed, PubMed, EMbase, Web of Science, and the Cochrane Library, covering records from database inception to 22 January 2025. Data analysis utilized Stata 18.0, R software (version 4.4.1), and Review Manager 5.4.ResultsA total of 100 randomized controlled trials (RCTs) were included, with a total sample size of 12,747 participants (6,639 in the experimental group and 6,108 in the control group), evaluating 12 distinct interventions. Network meta-analysis revealed the following optimal combinations: FeiJieHe Pill combined with standard biomedicine demonstrated superior efficacy for clinical response rate improvement (OR = 8.43, 95% CI [1.79, 39.69]). KangLao Pill combined with standard biomedicine was the most effective for negative conversion rate (OR = 11.55, 95% CI [3.04, 43.93]). Bu Jin Tablet combined with standard biomedicine demonstrated superior efficacy for lesion absorption rate (OR = 7.46, 95% CI [3.32, 16.75]). FeiJieHe Pill combined with standard biomedicine was the most effective for cavity absorption (OR = 5.11, 95% CI [2.04, 12.85]). JieHe Pill combined with conventional biomedicine yielded the greatest improvement in both CD3+ T lymphocyte response (OR = 5.6, 95% CI [3.4, 7.8]) and CD4+ T lymphocyte response (OR = 5.1, 95% CI [2.9, 7.3]).ConclusionCombination therapy utilizing oral CCPP alongside conventional biomedicine has a significant enhanced efficacy relative to conventional biomedicine monotherapy across multiple tuberculosis treatment metrics, including clinical efficacy rate, negative conversion rate, lesion absorption rate, cavity absorption rate, and improvement rates of CD3+ and CD4+ T lymphocyte levels.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024589122, identifier CRD42024589122.